2020
DOI: 10.3390/s20051360
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea Detection with Polysomnography and Depth Sensors

Abstract: This paper is devoted to proving two goals, to show that various depth sensors can be used to record breathing rate with the same accuracy as contact sensors used in polysomnography (PSG), in addition to proving that breathing signals from depth sensors have the same sensitivity to breathing changes as in PSG records. The breathing signal from depth sensors can be used for classification of sleep apnea events with the same success rate as with PSG data. The recent development of computational technologies has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The characterization of chest wall motion has been addressed in many methodological works, which presented interesting results, including for the general (e.g., motion quantification) and specific levels (e.g., illness detection/severity assessment and scoring). This can be grouped as follows: [ 57 , 61 , 62 , 64 , 68 , 72 , 117 , 120 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ] (2010–2015), [ 3 , 10 , 47 , 48 , 49 , 53 , 54 , 95 , 97 , 99 , 101 , 105 , 111 , 122 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characterization of chest wall motion has been addressed in many methodological works, which presented interesting results, including for the general (e.g., motion quantification) and specific levels (e.g., illness detection/severity assessment and scoring). This can be grouped as follows: [ 57 , 61 , 62 , 64 , 68 , 72 , 117 , 120 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ] (2010–2015), [ 3 , 10 , 47 , 48 , 49 , 53 , 54 , 95 , 97 , 99 , 101 , 105 , 111 , 122 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ...…”
Section: Resultsmentioning
confidence: 99%
“…Schätz et al used a variety RGB-D sensor, including the D415, and D435 ASV sensors to capture the breathing rate of a sleeping person [ 111 ]. Authors showed that depth sensors could be used to record breathing rate with the same accuracy as contact sensors used in polysomnography (PSG).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, sleep apnea can be detected with a mobile phone built-in microphone [81,82]. Other available techniques for apnea monitoring include the use of camera sensors for the recording of surveillance videos that can be post-processed to retrieve apnea episodes [83,84]. Besides, techniques based on instrumented items (e.g., sleep mats) have also been designed and tested, but further research is needed to improve their sensitivity to sleep apnea detection [85].…”
Section: Measurement and Computingmentioning
confidence: 99%
“…The authors came to the conclusion that body-conducted sensor performs better in four different types of the experiments. Schatz et al [ 3 ] studied the application of five different types of depth sensors for breathing rate monitoring and usage of this data for the sleep apnea identification. All of the sensors output were compared with the reference sensor and two of the five sensors have been found appropriate for sleep apnea determination.…”
Section: Introductionmentioning
confidence: 99%